2009
DOI: 10.2116/xraystruct.25.127
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Crystal Structure of 2-[(E)-2-(4-Ethoxyphenyl)ethenyl]-1-methylpyridinium 4-methylbenzenesulfonate monohydrate

Abstract: Non-linear optics (NLO) has been recognized for several decades as being a promising field with important applications in the domain of opto-electronics and photonics. [1][2][3][4][5] From a literature review we know that a generally popular approach towards NLO materials is to synthesize those compounds that have extended conjugated systems with donor and acceptor groups. However, the mentioned approach will not be affected if the compound crystallizes in a centrosymmetric space group, since the second-order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…For background literature concerning molecular-ionic compounds, see: Czupinski et al (2002); Katrusiak & Szafranski (2006). For related structures, see: Chanawanno et al (2009); Chantrapromma et al (2010); Collier et al (2006); Fun et al (2010); Kobkeatthawin et al (2009); Li et al (2005)…”
Section: Related Literaturementioning
confidence: 99%
“…For background literature concerning molecular-ionic compounds, see: Czupinski et al (2002); Katrusiak & Szafranski (2006). For related structures, see: Chanawanno et al (2009); Chantrapromma et al (2010); Collier et al (2006); Fun et al (2010); Kobkeatthawin et al (2009); Li et al (2005)…”
Section: Related Literaturementioning
confidence: 99%
“…For molecular salts as solid forms in pharmaceutical formulations, see: Stahl & Wermuth (2002). For related structures, see: Chanawanno et al (2009); Chantrapromma et al (2010); Collier et al (2006); Fun et al (2010); Li et al (2005); Lin (2010); Tabatabaee & Noozari (2011); Wu et al (2009). For standard bond lengths, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…In the title compound, the proton of the sulfonic group of sulfonic acid has been transferred to the N atom of the 3-fluoroaniline molecule, leading to the formation of the molecular complex, (I). Crystal structures of some benzenesulfonate derivatives, viz., 2,4,6-triamino-1,3,5-triazin-1-ium 4-methylbenzenesulfonate monohydrate (Li et al, 2005), ephedrine besylate (Collier et al, 2006), 2-ethyl-6-methylanilinium 4-methylbenzenesulfonate (Wu et al, 2009), 2-[(E)-2-(4-ethoxyphenyl)ethenyl]-1methylpyridinium 4-methylbenzenesulfonate monohydrate (Chanawanno et al, 2009), 2-aminopyrimidin-1-ium 4methylbenzenesulfonate (Tabatabaee & Noozari, 2011), 4-(cyanomethyl)anilinium 4-methylbenzenesulfonate monohydrate (Lin, 2010), 1-methyl-2-[(E)-2-(2-thienyl)etheny] quinolinium 4-bromobenzenesulfonate (Fun et al, 2010) and (E)-2-[4-(dimethylamino)styryl]-1-methylpyridinium 4-methylbenzenesulfonate monohydrate have been reported. In view of the importance of benzenesulphonic acid, we report herein the crystal structure of the title compound (I).…”
Section: S1 Commentmentioning
confidence: 99%
“…For background to molecular-ionic compounds, see: Czupinski et al (2002); Katrusiak & Szafranski (2006). For related structures, see: Chanawanno et al (2009); ; Collier et al (2006); Fun et al (2010); Li et al (2005); Lin (2010); Tabatabaee & Noozari (2011); Wu et al (2009). For normal bond lengths in organic compounds, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…A variety of pharmaceutical drugs are prepared as salts of benzenesulfonic acid and are known as besylates. Crystal structures of some benzenesulfonate derivatives, viz., 2,4,6-triamino-1,3,5-triazin-1-ium 4methylbenzenesulfonate monohydrate (Li et al, 2005), ephedrine besylate (Collier et al, 2006), 2-ethyl-6-methylanilinium 4-methylbenzenesulfonate (Wu et al, 2009), 2-[(E)-2-(4-ethoxyphenyl)ethenyl]-1-methylpyridinium 4-methylbenzenesulfonate monohydrate (Chanawanno et al, 2009), 2-aminopyrimidin-1-ium 4-methylbenzenesulfonate (Tabatabaee & Noozari, 2011), 4-(cyanomethyl)anilinium 4-methylbenzenesulfonate monohydrate (Lin, 2010) (Fun et al, 2010) and (E)-2-[4-(dimethylamino)styryl]-1-methylpyridinium 4-methylbenzenesulfonate monohydrate (Chantrapromma et al, 2010) have been reported. In view of the importance of benzenesulphonic acid, we report herein the crystal structure of the title compound (I).…”
Section: S1 Commentmentioning
confidence: 99%